Forms of Practitioner Research. (17th April 2017) - Shaw, Ian; Lunt, Neil
Abstract: Τhe aim of this paper is to draw on evidence to identify distinctions within those forms of research which are to significant degrees practitioner-engaged. The research review on which this is based took place in the fields of health, social care and social work. We suggest there are different forms of practitioner research, and that using a blanket term for all instances of such inquiry may confuse rather than enlighten. Drawing from the data, we characterise these as 'practitioner-led' and 'academic-partnership' research. We set out a range of distinctions with regard to the occupational roles of researchers, research relationships, writing relationships, the focus of the research questions and problems, research methodology, the extent to which benefits and utilisation are addressed, and the writing 'voice' in published outputs. We conclude that the policy and practice implications ought not to be cast in stone through any regulatory framework, but should be seen as implying a flexible and enabling reference point. Practitioner research should not be petrified in ways that suit the dominant identity of this or that professional community.